PENGARUH MANAJEMEN MUTU DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RSUD KABUPATEN KARANGANYAR - Eko Sutopo; Sudarwati Sudarwati; Istiqomah Istiqomah (ITB AAS INDONESIA Surakarta, 2019)
The purpose of this study was to find out: the effect of service quality, reliability, responsiveness, and empathy both jointly and partially on the satisfaction of inpatients in the Karanganyar District Hospital. Judging from the type or type, this research is explanatory research (explanation). The population in this study were 1006 patients hospitalized in Karanganyar Hospital. As a sample 100 people were taken using proportional random sampling technique. The data collection technique used is by questionnaire method, documentation and literature study. The data analysis technique in this study is the classic assumption test, multiple linear regression analysis, t test, F test and coefficient of determination. Based on the results of the tests that have been carried out it can be concluded as follows: (1) There is a positive and significant effect simultaneously management of quality, reliability, responsiveness, and empathy on the satisfaction of inpatients in Karanganyar District Hospital. (2) There is a positive and significant effect of partial quality management on the satisfaction of inpatients in the RSUD. (3) There is a positive and significant partial effect of reliability on the satisfaction of inpatients in the RSUD. (4) There is a positive and significant influence partially on responsiveness to the satisfaction of inpatients in the RSUD. (5) There is a positive and significant partial effect of empathy on the satisfaction of inpatients in the RSUD. Keywords: quality management, reliability, responsiveness, empathy, patient satisfaction